The genetic etiology of critical congenital heart disease - Mendha Aishwarya (Annals of Circulation - Peertechz Publications, 2022)
Congenital Heart Disease (CHD) is the most common kind of birth defect. Congenital heart disease is the most common birth defect and the leading cause of death in newborns. The causes of CHD are complicated and involve both genes and the environment. Congenital heart disease includes problems with the septum, the valves, and the outflow tract. Correctional heart surgery and new strategies for managing CHD have massively enhanced life expectancy. 490 percent of CHD newborns who live through their first year will become adults. Studies of the molecular genetics of humans and animal models of development are enhancing our understanding of normal heart development and cardiac diseases. A recent study demonstrates that microRNAs are implicated in congenital heart diseases. Epigenetic variables were eventually revealed to influence heart development. Several genes are responsible for congenital cardiac abnormalities as well as genetic disorders. This paper describes the categorization, environmental, and genetic causes of Coronary Heart Disease (CHD), the role of key CHD-causing genes, and potential options for preventing CHD.